Exchange Rate Pass-Through to Food and Energy Consumer Price Inflation - Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies exchange rate pass-through to food and energy consumer price inflation and its dependence on the inflation environment using cross-country panel estimation of Phillips curves. It considers a large panel of OECD member and candidate economies with quarterly data from 1994 to 2021. We find that exchange rate pass-through is largest for energy CPI inflation and also significant for food CPI inflation. A 10% depreciation in the exchange rate leads to an increase in energy CPI inflation of around 2 percentage points (pp) at the quarterly horizon and of 4pp at the yearly horizon; it leads to an increase in food CPI inflation of around 0.3pp and 2pp at the quarterly and yearly horizon, respectively. We also find some evidence that exchange rate pass-through to food and energy CPI inflation depends on the inflation environment, with higher inflation leading to larger pass-through.
Keywords: E31; E52; E58; F31; 330; inflation; food prices; energy prices; exchange rates